Juvenile xanthogranuloma manifesting with LCH‐associated neurodegenerative disease‐like radiological findings - Daifu, Tomoo; Umeda, Katsutsugu; Yokoyama, Atsushi; Yoshida, Takeshi; Saida, Satoshi; Kato, Itaru; Hiramatsu, Hidefumi; Kudo, Ko; Higuchi, Yoshihisa; Takita, Junko (Pediatric blood & cancer, 2024)
Here, we describe two patients with juvenile xanthogranuloma (JXG) manifesting with Langerhans cell histiocytosis (LCH)‐associated neurodegenerative disease (ND)‐like radiological findings. One patient showed typical radiological abnormalities at onset, which worsened with progressing central nervous system symptoms 7 years after LCH‐oriented chemotherapy. Another showed spontaneous regression of clinical symptoms, with a transient radiological change 1 year after salvage chemotherapy for recurrence of JXG. These data regarding JXG‐associated ND will facilitate future investigation of the disease, as well as development of therapeutic interventions.